Enhanced renoprotective effects of combined glucagon‐like peptide‐1 receptor agonists and sodium‐glucose cotransporter 2 inhibitors in type 2 diabetes mellitus: Real‐world evidence - Jian‐Yu Jhu; Yu‐Wei Fang; Chung‐Yen Huang; Hung‐Hsiang Liou; Mon‐Ting Chen; Ming‐Hsien Tsai (Journal of Diabetes Investigation)
ABSTRACT Introduction Developing a more effective treatment for the global impact of diabetic kidney disease is crucial. This study examined the renoprotective effects of combining glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA) with sodium–glucose cotransporter 2 inhibitors (SGLT2i) compared to SGLT2is alone in type 2 diabetes (DM). Materials and Methods This retrospective cohort study used data from the TriNetX Global Collaborative Network. Type 2 DM patients with estimated glomerular filtration rates ≥60 mL/min/1.73 m2 who used GLP‐1 RA or SGLT2i between January 1, 2013, and December 31, 2023. Propensity score matching balanced baseline characteristics, resulting in 71,186 patients in each group (combined GLP‐1 RA and SGLT2i therapy vs SGLT2i alone). Cox regression model was adopted to compare outcomes over a 5‐year period, including major adverse kidney events (MAKE), acute kidney injury (AKI), end‐stage kidney disease (ESKD), and all‐cause mortality. Results After matching, the average age was 57.1 ± 10.8 years for the GLP‐1 RA plus SGLT2i group and 57.2 ± 11.7 years for the SGLT2i‐only group. The GLP‐1 RA plus SGLT2i group had significantly lower risk of MAKE (hazard ratio [HR]: 0.73, 95% confidence interval [CI]: 0.69–0.77), AKI (HR: 0.82, 95% C0I: 0.77–0.87), ESKD (HR: 0.61, 95% CI: 0.47–0.78), and all‐cause mortality (HR: 0.54, 95% CI: 0.50–0.58) compared to the SGLT2i‐only group. Moreover, subgroup analyses showed consistent benefits across different subgroups. Conclusions Dual therapy with GLP‐1 RA and SGLT2i is supported to enhance renal outcomes and address the growing burden of diabetic kidney disease.